2016
DOI: 10.5507/bp.2015.067
|View full text |Cite
|
Sign up to set email alerts
|

Factors underlying elevated troponin I levels following pacemaker primo-implantation

Abstract: Background. Cardiac troponins are routinely used as markers of myocardial damage. Originally, they were only intended for use in diagnosing acute coronary syndromes; however, we now know that raised serum troponin levels are not always caused by ischemia. There are many other clinical conditions that cause damage to cardiomyocytes, leading to raised levels of troponin. However, the specificity of cardiac troponins towards the myocardium is absolute. Our work focuses on mechanical damage to the myocardium and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Permanent pacemaker implantation is accomplished by transvenous insertion of endocardial leads. A number of studies have demonstrated that the mechanical effect of lead fixation on the myocardium may cause local injury, as evidenced by raised levels of plasma troponin and inflammatory biomarkers 1,2 . It is reported that transvenous insertion of the leads is followed by a sequence of cardiac histopathological changes, leading eventually to the formation of a fibrous connective tissue scar 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Permanent pacemaker implantation is accomplished by transvenous insertion of endocardial leads. A number of studies have demonstrated that the mechanical effect of lead fixation on the myocardium may cause local injury, as evidenced by raised levels of plasma troponin and inflammatory biomarkers 1,2 . It is reported that transvenous insertion of the leads is followed by a sequence of cardiac histopathological changes, leading eventually to the formation of a fibrous connective tissue scar 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Rapid increase and decrease in cardiac troponin plasma levels are characteristic of reversible myocardial mechanical injury, especially due to the physical contact between lead and endocardium, resulting in direct cardiomyocyte destruction during the implantation procedure [1,2] . A small percentage of troponin is found in the myocyte cytoplasm in a soluble free form, which is released into the circulation under such circumstances [5] . A rapid troponin washout occurs within 24 hours, as there is no obstructive myocardial blood flow [3,4,6] .…”
Section: Discussionmentioning
confidence: 99%
“…Permanent pacemaker implantation is accomplished by transvenous insertion of endocardial leads, whose stability is secured and maintained using either active or passive fixation. A number of studies have demonstrated that the mechanical effect of both lead fixation types on the myocardium may lead to local injury, as evidenced by raised levels of plasma troponin and inflammatory biomarkers [1][2][3][4][5][6][7][8][9]12] . However, data are scarce regarding the association of the lead fixation type (active or passive) with the extent of myocardial injury, the subsequent systemic inflammatory response, and the possible clinical significance of cardiac biomarkers elevation, as clinical adverse events or abnormal change in pacing parameters.…”
Section: Introductionmentioning
confidence: 99%